Antenna arrays in mobile communications gain, diversity, and channel capacity. - Andersen, Jergen Bach (IEEE Antennas & propagation magazine.)
Are antenna arrays in mobile communications different from arrays in other applications? The answer is yes, sometimes, and it is the purpose of this paper to explain, in a tutorial fashion, when this is the case, and what this means for path loss in link calculations. One aspect is the classical gain of an antenna, which we have to understand in a new way. Another aspect is the possibility for two arrays, in a scattering environment, to create parallel channels, and thus, in effect, act as many independent antennas at the same time, carrying much more traffic over the same bandwidth.